Research of stationary modes in the carbonization column for producing calcinated soda by ammonia method - Bobukh, Anatoly; Bolotynska, Oleksandra (Cognum Publishing House, United Kingdom, 2019)
This article discusses the control of the carbonization department of the production of producing calcinated soda by ammonia method. Analyzing information sources, as well as studies, stationary modes of the carbonization column were described. A study of stationary modes was carried out to decide on the appropriateness of their use for the separation of carbonization.
Keywords: carbonization; carbonization column; control; stationary mode; sodium hydrogen carbonate